Wear-resistant duplex stainless steel band and processing technology thereof

By coating the iron-nickel-copper layer on the surface of the duplex stainless steel belt and coating corrosion-resistant and antibacterial coating, and spraying the modified gallium zinc oxide layer, the corrosion resistance and wear resistance of duplex stainless steel belts are solved by introducing copper. The problem of this achieves better antibacterial and corrosion resistance.

CN119287465AActive Publication Date: 2025-01-10JIANGSU YONGJIN METAL TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411806218.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-01-10
Estimated Expiration
2044-12-10

AI Technical Summary

Technical Problem

When existing duplex stainless steel strips are introduced to improve antibacterial ability, corrosion resistance and surface wear resistance will decrease, and the coated antibacterial coatings are poorly combined, which will affect product performance and life.

Method used

The surface of duplex stainless steel strip is coated with an iron-nickel-copper layer, and a corrosion-resistant antibacterial coating containing nano silicon carbide and corrosion-resistant antibacterial agent is then modified and sprayed in the gallium zinc oxide sol to form a gallium-containing coating. Zinc oxide layer improves binding strength and antibacterial properties through heat treatment.

Benefits of technology

It improves the antibacterial and wear resistance of stainless steel strips, while maintaining corrosion resistance, avoids the degradation of the thermal processing performance of copper plating, and enhances the bonding force between the plating and the substrate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of stainless steel bands, and particularly discloses a wear-resistant duplex stainless steel band and a processing technology thereof. The method specifically comprises the following steps that S1, the surface of a duplex stainless steel band is electroplated with an iron-nickel-copper layer, and a stainless steel band A is obtained; the plating solution comprises the following components: 40-50 g / L of nickel sulfate hexahydrate, 20-30 g / L of ferric sulfate, 30-40 g / L of copper sulfate pentahydrate, 35-45 g / L of sodium citrate dehydrate, 25-30 g / L of sodium acetate and 20-25 g / L of sodium hypophosphite; s2, uniformly mixing organic silicon resin, hydrogen-containing silicone oil, ethanol, nano silicon carbide and a corrosion-resistant antibacterial agent to obtain a corrosion-resistant antibacterial coating; s3, the surface of the stainless steel band A is coated with the corrosion-resistant antibacterial coating, drying is conducted at the room temperature, and a stainless steel band B with a corrosion-resistant antibacterial coating on the surface is obtained; and coating gallium-containing zinc oxide sol on the surface of the stainless steel band B, and carrying out heat treatment to obtain the wear-resistant duplex stainless steel band with a gallium-containing zinc oxide layer on the surface.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of stainless steel strips, and in particular discloses a wear-resistant duplex stainless steel strip and a processing technology thereof. Background Art

[0002] Stainless steel strips made of duplex stainless steel have the characteristics of both ferritic stainless steel and austenitic stainless steel, and their mechanical properties and corrosion resistance are better than those of traditional austenitic and ferritic stainless steels. With the continuous development of the economy and the continuous improvement of people's quality of life, stainless steel strips are required to have better performance.

[0003] In order to improve the antibacterial ability of stainless steel strips, copper is often introduced into duplex stainless steel; however, whether copper is introduced into the stainless steel matrix or copper is plated on the surface, it will lead to a decrease in corrosion resistance, surface wear resistance and other properties, affecting the performance and life of the product. However, coating the surface with corrosion-resistant and antibacterial coatings has the problem of poor bonding. Therefore, it is of great significance to study a wear-resistant duplex stainless steel strip with good corrosion resistance and antibacterial properties and its processing technology. Summary of the invention

[0004] The object of the present invention is to provide a wear-resistant duplex stainless steel strip and a processing technology thereof to solve the problems raised in the prior art.

[0005] To achieve the above object, the present invention provides the following technical solution: A processing technology for wear-resistant duplex stainless steel strip, comprising the following steps: S1: electroplating an iron-nickel-copper layer on the surface of the duplex stainless steel strip to obtain a stainless steel strip A; S2: taking organic silicone resin, hydrogenated silicone oil, ethanol, nano silicon carbide, and corrosion-resistant antibacterial agent, and mixing them evenly to obtain corrosion-resistant antibacterial coating; S3: coating the surface of the stainless steel strip A with a corrosion-resistant and antibacterial coating, and drying the surface of the stainless steel strip B with a corrosion-resistant and antibacterial coating; coating the surface of the stainless steel strip B with a gallium-containing zinc oxide sol, and heat treating the surface of the stainless steel strip B to obtain a wear-resistant duplex stainless steel strip with a gallium-containing zinc oxide layer.

[0006] More optimally, the heat treatment includes the following steps: treatment at 90-100°C for 4-6 hours and treatment at 200-220°C for 25-30 minutes.

[0007] More optimally, the electroplating process is: pH = 7-8, temperature 55-60°C, DC current 3-5A / dm 3 , time 20~30min; the plating solution used for electroplating includes the following components: 40~50g / L nickel sulfate hexahydrate, 20~30g / L ferric sulfate, 30~40g / L copper sulfate pentahydrate, 35~45g / L sodium citrate dihydrate, 25~30g / L sodium acetate, 20~25g / L sodium hypophosphite.

[0008] More optimally, the corrosion-resistant and antibacterial coating comprises the following raw materials, calculated by mass: 75-85 parts of silicone resin, 10-15 parts of hydrogenated silicone oil, 10-15 parts of ethanol, 25-35 parts of nano-silicon carbide, and 10-15 parts of corrosion-resistant and antibacterial agent.

[0009] More optimally, the preparation of the corrosion-resistant antibacterial agent includes the following steps: Step 1: adding hexadecylamine and aluminum dihydrogen tripolyphosphate to water, adding a mixed solution of water and organic amine, stirring at room temperature for 1 to 2 hours, filtering, washing, drying, and grinding to obtain hexadecylamine intercalated aluminum dihydrogen tripolyphosphate; Step 2: Take hexadecylamine intercalated with aluminum dihydrogen tripolyphosphate and ether, pressurize and heat to 85-90°C and stir evenly, add 3,4-dihydroxycinnamaldehyde, stir for 30-40 minutes, add glacial acetic acid, react for 4-6 hours, remove the solvent, and obtain an intermediate; Step 3: Take the intermediate, 5,6-dibromobenzimidazole, guar gum hydroxypropyltrimethylammonium chloride and sodium carbonate, add them to ethanol and stir evenly, stir at 70-78°C for 5-7h, remove the solvent, and obtain a corrosion-resistant antibacterial agent.

[0010] More optimally, the hexadecylamine intercalated aluminum dihydrogen tripolyphosphate comprises the following raw materials, calculated by weight: 2-3 parts of hexadecylamine, 3-4 parts of aluminum dihydrogen tripolyphosphate, and 20-30 parts of a mixed solution; the mixed solution is a solution of water and an organic amine in a volume ratio of (3-4): 1; The intermediate comprises the following raw materials, calculated by weight: 8 to 10 parts of hexadecylamine intercalated aluminum dihydrogen tripolyphosphate, 4 to 6 parts of 3,4-dihydroxycinnamaldehyde, and 2 to 3 parts of glacial acetic acid; The corrosion-resistant antibacterial agent comprises the following raw materials, calculated by weight: 4 to 5 parts of an intermediate, 4.5 to 6 parts of 5,6-dibromobenzimidazole, 2 to 3 parts of guar gum hydroxypropyltrimethylammonium chloride, and 2 to 3 parts of sodium carbonate.

[0011] More optimally, the mixed solution is a solution of water and n-propylamine in a volume ratio of 3:1.

[0012] More optimally, the preparation of the gallium-containing zinc oxide sol includes the following steps: taking zinc nitrate, zinc acetylacetonate, gallium nitrate, and ethanol, stirring evenly at 50-60° C., and aging for 24-25 hours to obtain a gallium-containing zinc oxide sol; in the gallium-containing zinc oxide sol, the concentration of zinc nitrate is 0.1-0.15 mol / L, the concentration of gallium nitrate is 0.002-0.003 mol / L, and the concentration of zinc acetylacetonate is 0.1-0.15 mol / L.

[0013] More optimally, the gallium-containing zinc oxide sol is modified to obtain a modified gallium-containing zinc oxide sol and then coated. The preparation of the modified gallium-containing zinc oxide sol includes the following steps: adding vinyltriethoxysilane to water, stirring evenly, adding the gallium-containing zinc oxide sol, stirring at 45-50° C. for 4-6 hours, adding a platinum catalyst, stirring evenly, and obtaining a modified gallium-containing zinc oxide sol.

[0014] More optimally, the modified gallium-containing zinc oxide sol includes the following raw materials, calculated by weight: 2-4 parts of vinyltriethoxysilane, 10-15 parts of water, 100-110 parts of gallium-containing zinc oxide sol, and 0.006-0.008 parts of platinum catalyst.

[0015] More optimally, the thickness of the corrosion-resistant and antibacterial coating is 10-15 μm; the thickness of the gallium-containing zinc oxide layer is 60-80 nm.

[0016] More optimally, the composition of the duplex stainless steel strip is as follows by mass percentage: C 0.001-0.002%; Cr23-25%; Mn 8-9%; N 0.5-0.7%; Ni 0.001-0.005%; the remainder is iron and other inevitable impurities.

[0017] More optimally, the duplex stainless steel strip has a thickness of 0.5-0.8 mm.

[0018] Preferably, the duplex stainless steel strip has a thickness of 0.6 mm.

[0019] Compared with the prior art, the beneficial effects achieved by the present invention are as follows: first, an iron-nickel-copper layer is plated on the surface of a duplex stainless steel strip to obtain a stainless steel strip A; due to the presence of iron and nickel, the coating has good bonding strength with the duplex stainless steel strip and the coating is flat, and the layer is used as a base layer, which is beneficial to the subsequent steps; copper has an antibacterial effect, but the antibacterial effect is poor when the bacterial concentration is high, and the corrosion resistance and wear resistance need to be further improved; A corrosion-resistant and antibacterial coating is applied on the surface of a stainless steel strip A to obtain a stainless steel strip B having a corrosion-resistant and antibacterial coating on the surface; wherein: aluminum dihydrogen tripolyphosphate can release tripolyphosphate ions with strong complexing ability, has strong bonding with the metal layer, and can form a dense corrosion-resistant film, in which hexadecylamine is intercalated to introduce amino groups so that it can participate in the next step of the reaction with the aldehyde group of 3,4-dihydroxycinnamaldehyde; first, the hydrophilic aldehyde group combines with the hydrophobic long carbon chain alkyl of hexadecylamine to form an amphiphilic structure, which can more effectively bind to the bacterial surface and enhance the antibacterial effect. And 3,4-dihydroxycinnamaldehyde can also provide corrosion resistance and antibacterial effects; 5,6-dibromobenzimidazole and guar gum hydroxypropyltrimethylammonium chloride are introduced in the next step of modification; the benzimidazole structure has both corrosion inhibition and antibacterial effects; guar gum hydroxypropyltrimethylammonium chloride can improve the overall dispersibility as a dispersant, and can further enhance the antibacterial ability, and can also be used as a thickener to adjust the viscosity; in summary, the corrosion-resistant antibacterial agent has a good corrosion-resistant and antibacterial effect, and has good dispersibility in the corrosion-resistant and antibacterial coating, and good bonding with the metal layer; In order to further improve the antibacterial and wear resistance, gallium-containing zinc oxide sol is introduced; gallium can effectively inhibit the proliferation of bacteria when it precipitates ions, but adding it to the stainless steel matrix may lead to a decrease in hot processing performance and cold forming performance; electroplating of gallium is difficult, and if it is introduced by electroplating, the uneven coating will cause a decrease in corrosion resistance and wear resistance, so the present invention combines it with zinc oxide and then sprays it onto the surface of the stainless steel strip; because the gallium-containing zinc oxide sol of the present invention is modified by vinyltriethoxysilane and contains double bonds, and hydrogen-containing silicone oil is added to the upper corrosion-resistant and antibacterial layer, the two can undergo an addition reaction under the catalysis of a platinum catalyst during heat treatment, thereby improving the bonding strength of the two layers, improving the antibacterial property of the stainless steel strip while improving the wear resistance. DETAILED DESCRIPTION

[0020] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0021] The following parts are by mass unless otherwise specified; The composition of the duplex stainless steel strip is as follows by mass percentage: C 0.001%; ​​Cr 24%; Mn 8.5%; N0.5%; Ni 0.002%; the remainder is iron and other inevitable impurities; Electroplating process: temperature is 60°C, DC current density is 4A / dm 3The plating time was 25 min. The plating solution included the following ingredients: 45 g / L nickel sulfate hexahydrate, 25 g / L ferric sulfate, 38 g / L copper sulfate pentahydrate, 42 g / L sodium citrate dihydrate, 28 g / L sodium acetate, and 25 g / L sodium hypophosphite; pH = 7; Example 1: S1: electroplating an iron-nickel-copper layer on the surface of a duplex stainless steel strip to obtain a stainless steel strip A; S2: Take zinc nitrate, zinc acetylacetonate, gallium nitrate and ethanol, stir evenly at 60°C, and age for 24 hours to obtain a gallium-containing zinc oxide sol; wherein the concentration of zinc nitrate in the ratio solution is 0.1 mol / L, the concentration of gallium nitrate is 0.002 mol / L, and the concentration of zinc acetylacetonate is 0.1 mol / L; S3: Take 3 parts of vinyl triethoxysilane, add to 12 parts of water, stir at 50°C for 0.5h, add 100 parts of gallium-containing zinc oxide sol, stir at 50°C for 5h, add 0.008 parts of platinum catalyst, stir evenly, and obtain modified gallium-containing zinc oxide sol; S4: Add 3 parts of hexadecylamine and 4 parts of aluminum dihydrogen tripolyphosphate to 15 parts of water, add 30 parts of the mixed solution, stir at room temperature for 2 hours, filter, wash, dry and grind to obtain hexadecylamine intercalated aluminum dihydrogen tripolyphosphate; S5: Take 10 parts of hexadecylamine intercalated aluminum tripolyphosphate and 150 parts of ether, pressurize and heat to 90°C and stir evenly, add 6 parts of 3,4-dihydroxycinnamaldehyde, stir for 30 minutes, add 3 parts of glacial acetic acid, react for 6 hours, remove the solvent, and obtain an intermediate; take 5 parts of the intermediate, 5 parts of 5,6-dibromobenzimidazole, 2 parts of guar gum hydroxypropyltrimethylammonium chloride, and 3 parts of sodium carbonate, add to 100 parts of ethanol and stir evenly, stir at 78°C for 6 hours, remove the solvent, and obtain a corrosion-resistant antibacterial agent; S6: Take 80 parts of silicone resin, 12 parts of hydrogenated silicone oil, 15 parts of ethanol, 30 parts of nano silicon carbide, and 12 parts of corrosion-resistant antibacterial agent, mix them evenly, and obtain a corrosion-resistant antibacterial coating; S7: The corrosion-resistant and antibacterial coating is applied to the surface of the stainless steel strip A to obtain a corrosion-resistant and antibacterial coating with a thickness of 12 μm, and the stainless steel strip B is obtained by ventilation and drying at room temperature for 2 days; the modified gallium-containing zinc oxide sol is applied to the surface of the stainless steel strip B, and the gallium-containing zinc oxide layer is obtained by treating the surface at 95° C. for 6 h and at 220° C. for 30 min, and the gallium-containing zinc oxide layer is obtained with a thickness of 70 nm, and the wear-resistant duplex stainless steel strip is obtained.

[0022] Example 2: S1: electroplating an iron-nickel-copper layer on the surface of a duplex stainless steel strip to obtain a stainless steel strip A; S2: Take zinc nitrate, zinc acetylacetonate, gallium nitrate and ethanol, stir evenly at 60°C, and age for 24 hours to obtain a gallium-containing zinc oxide sol; wherein the concentration of zinc nitrate in the ratio solution is 0.1 mol / L, the concentration of gallium nitrate is 0.002 mol / L, and the concentration of zinc acetylacetonate is 0.1 mol / L; S3: Take 2 parts of vinyl triethoxysilane, add to 10 parts of water, stir at 50°C for 0.5h, add 100 parts of gallium-containing zinc oxide sol, stir at 50°C for 5h, add 0.008 parts of platinum catalyst, stir evenly, and obtain modified gallium-containing zinc oxide sol; S4: Add 2 parts of hexadecylamine and 3 parts of aluminum dihydrogen tripolyphosphate to 15 parts of water, add 30 parts of the mixed solution, stir at room temperature for 2 hours, filter, wash, dry and grind to obtain hexadecylamine intercalated aluminum dihydrogen tripolyphosphate; S5: Take 8 parts of hexadecylamine intercalated aluminum tripolyphosphate and 150 parts of ether, pressurize and heat to 90°C and stir evenly, add 4 parts of 3,4-dihydroxycinnamaldehyde, stir for 30 minutes, add 2 parts of glacial acetic acid, react for 6 hours, remove the solvent, and obtain an intermediate; take 4 parts of the intermediate, 4.5 parts of 5,6-dibromobenzimidazole, 2 parts of guar gum hydroxypropyltrimethylammonium chloride, and 2 parts of sodium carbonate, add to 100 parts of ethanol and stir evenly, stir at 78°C for 6 hours, remove the solvent, and obtain a corrosion-resistant antibacterial agent; S6: Take 85 parts of silicone resin, 10 parts of hydrogenated silicone oil, 15 parts of ethanol, 30 parts of nano silicon carbide, and 15 parts of corrosion-resistant antibacterial agent, mix them evenly, and obtain a corrosion-resistant antibacterial coating; S7: The corrosion-resistant and antibacterial coating is applied to the surface of the stainless steel strip A to obtain a corrosion-resistant and antibacterial coating with a thickness of 12 μm, and the stainless steel strip B is obtained by ventilation and drying at room temperature for 2 days; the modified gallium-containing zinc oxide sol is applied to the surface of the stainless steel strip B, and the gallium-containing zinc oxide layer is obtained by treating the surface at 95° C. for 6 h and at 220° C. for 30 min, and the gallium-containing zinc oxide layer is obtained with a thickness of 70 nm, and the wear-resistant duplex stainless steel strip is obtained.

[0023] Example 3: S1: electroplating an iron-nickel-copper layer on the surface of a duplex stainless steel strip to obtain a stainless steel strip A; S2: Take zinc nitrate, zinc acetylacetonate, gallium nitrate and ethanol, stir evenly at 60°C, and age for 24 hours to obtain a gallium-containing zinc oxide sol; wherein the concentration of zinc nitrate in the ratio solution is 0.1 mol / L, the concentration of gallium nitrate is 0.002 mol / L, and the concentration of zinc acetylacetonate is 0.1 mol / L; S3: Take 4 parts of vinyl triethoxysilane, add to 15 parts of water, stir at 50°C for 0.5h, add 100 parts of gallium-containing zinc oxide sol, stir at 50°C for 5h, add 0.008 parts of platinum catalyst, stir evenly, and obtain modified gallium-containing zinc oxide sol; S4: Add 3 parts of hexadecylamine and 4 parts of aluminum dihydrogen tripolyphosphate to 15 parts of water, add 30 parts of the mixed solution, stir at room temperature for 2 hours, filter, wash, dry and grind to obtain hexadecylamine intercalated aluminum dihydrogen tripolyphosphate; S5: Take 10 parts of hexadecylamine intercalated aluminum tripolyphosphate and 150 parts of ether, pressurize and heat to 90°C and stir evenly, add 6 parts of 3,4-dihydroxycinnamaldehyde, stir for 30 minutes, add 3 parts of glacial acetic acid, react for 6 hours, remove the solvent, and obtain an intermediate; take 5 parts of the intermediate, 6 parts of 5,6-dibromobenzimidazole, 3 parts of guar gum hydroxypropyltrimethylammonium chloride, and 3 parts of sodium carbonate, add to 100 parts of ethanol and stir evenly, stir at 78°C for 6 hours, remove the solvent, and obtain a corrosion-resistant antibacterial agent; S6: Take 75 parts of silicone resin, 15 parts of hydrogenated silicone oil, 15 parts of ethanol, 35 parts of nano-silicon carbide, and 10 parts of corrosion-resistant antibacterial agent, mix them evenly, and obtain a corrosion-resistant antibacterial coating; S7: The corrosion-resistant and antibacterial coating is applied to the surface of the stainless steel strip A to obtain a corrosion-resistant and antibacterial coating with a thickness of 12 μm, and the stainless steel strip B is obtained by ventilation and drying at room temperature for 2 days; the modified gallium-containing zinc oxide sol is applied to the surface of the stainless steel strip B, and the gallium-containing zinc oxide layer is obtained by treating the surface at 95° C. for 6 h and at 220° C. for 30 min, and the gallium-containing zinc oxide layer is obtained with a thickness of 70 nm, and the wear-resistant duplex stainless steel strip is obtained.

[0024] Comparative Example 1 (using unmodified gallium-containing zinc oxide sol, and replacing hydrogen-containing silicone oil with organic silicone resin, and the remaining method steps are consistent with Example 1): S1: electroplating an iron-nickel-copper layer on the surface of a duplex stainless steel strip to obtain a stainless steel strip A; S2: Take zinc nitrate, zinc acetylacetonate, gallium nitrate and ethanol, stir evenly at 60°C, and age for 24 hours to obtain a gallium-containing zinc oxide sol; wherein the concentration of zinc nitrate in the ratio solution is 0.1 mol / L, the concentration of gallium nitrate is 0.002 mol / L, and the concentration of zinc acetylacetonate is 0.1 mol / L; S3: Add 3 parts of hexadecylamine and 4 parts of aluminum dihydrogen tripolyphosphate to 15 parts of water, add 30 parts of the mixed solution, stir at room temperature for 2 hours, filter, wash, dry and grind to obtain hexadecylamine intercalated aluminum dihydrogen tripolyphosphate; S4: Take 10 parts of hexadecylamine intercalated aluminum tripolyphosphate and 150 parts of ether, pressurize and heat to 90°C and stir evenly, add 6 parts of 3,4-dihydroxycinnamaldehyde, stir for 30 minutes, add 3 parts of glacial acetic acid, react for 6 hours, remove the solvent, and obtain an intermediate; take 5 parts of the intermediate, 5 parts of 5,6-dibromobenzimidazole, 2 parts of guar gum hydroxypropyltrimethylammonium chloride, and 3 parts of sodium carbonate, add to 100 parts of ethanol and stir evenly, stir at 78°C for 6 hours, remove the solvent, and obtain a corrosion-resistant antibacterial agent; S5: Take 92 parts of silicone resin, 15 parts of ethanol, 30 parts of nano silicon carbide, and 12 parts of corrosion-resistant antibacterial agent, mix them evenly, and obtain corrosion-resistant antibacterial coating; S6: The corrosion-resistant and antibacterial coating is applied to the surface of the stainless steel strip A to obtain a corrosion-resistant and antibacterial coating with a thickness of 12 μm, and the stainless steel strip B is obtained by ventilation and drying at room temperature for 2 days; the modified gallium-containing zinc oxide sol is applied to the surface of the stainless steel strip B, and the gallium-containing zinc oxide layer is obtained by treating the strip at 95°C for 6 hours and at 220°C for 30 minutes to obtain a gallium-containing zinc oxide layer with a thickness of 70 nm, thereby obtaining a wear-resistant duplex stainless steel strip.

[0025] Comparative Example 2 (electroplated an iron-nickel-copper-gallium-zinc layer on the surface of a stainless steel strip, without using a gallium-containing zinc oxide layer, and the remaining method steps are consistent with Example 1): S1: electroplated an iron-nickel-copper-gallium-zinc layer on the surface of a duplex stainless steel strip to obtain a stainless steel strip A; Electroplating process: temperature is 60°C, DC current density is 4A / dm 3 The plating time is 25 min; the plating solution includes the following ingredients: 45 g / L nickel sulfate hexahydrate, 25 g / L iron sulfate, 38 g / L copper sulfate pentahydrate, 42 g / L sodium citrate dihydrate, 5 g / L gallium chloride, 10 g / L zinc sulfate, 28 g / L sodium acetate, 25 g / L sodium hypophosphite; pH = 7; S2: Add 3 parts of hexadecylamine and 4 parts of aluminum dihydrogen tripolyphosphate to 15 parts of water, add 30 parts of the mixed solution, stir at room temperature for 2 hours, filter, wash, dry and grind to obtain hexadecylamine intercalated aluminum dihydrogen tripolyphosphate; S3: Take 10 parts of hexadecylamine intercalated aluminum tripolyphosphate and 150 parts of ether, pressurize and heat to 90°C and stir evenly, add 6 parts of 3,4-dihydroxycinnamaldehyde, stir for 30 minutes, add 3 parts of glacial acetic acid, react for 6 hours, remove the solvent, and obtain an intermediate; take 5 parts of the intermediate, 5 parts of 5,6-dibromobenzimidazole, 2 parts of guar gum hydroxypropyltrimethylammonium chloride, and 3 parts of sodium carbonate, add to 100 parts of ethanol and stir evenly, stir at 78°C for 6 hours, remove the solvent, and obtain a corrosion-resistant antibacterial agent; S4: Take 80 parts of silicone resin, 12 parts of hydrogenated silicone oil, 15 parts of ethanol, 30 parts of nano-silicon carbide, and 12 parts of corrosion-resistant antibacterial agent, mix them evenly, and obtain a corrosion-resistant antibacterial coating; S5: The corrosion-resistant and antibacterial coating is applied to the surface of the stainless steel strip A to obtain a corrosion-resistant and antibacterial coating with a thickness of 12 μm. The coating is dried at room temperature for 2 days, treated at 95° C. for 6 hours, and treated at 220° C. for 30 minutes to obtain a wear-resistant duplex stainless steel strip.

[0026] Comparative Example 3 (the preparation method of the corrosion-resistant antibacterial agent is changed, and the remaining method steps are consistent with Example 1): S1: electroplating an iron-nickel-copper layer on the surface of a duplex stainless steel strip to obtain a stainless steel strip A; S2: Take zinc nitrate, zinc acetylacetonate, gallium nitrate and ethanol, stir evenly at 60°C, and age for 24 hours to obtain a gallium-containing zinc oxide sol; wherein the concentration of zinc nitrate in the ratio solution is 0.1 mol / L, the concentration of gallium nitrate is 0.002 mol / L, and the concentration of zinc acetylacetonate is 0.1 mol / L; S3: Take 3 parts of vinyl triethoxysilane, add to 12 parts of water, stir at 50°C for 0.5h, add 100 parts of gallium-containing zinc oxide sol, stir at 50°C for 5h, add 0.008 parts of platinum catalyst, stir evenly, and obtain modified gallium-containing zinc oxide sol; S4: Add 3 parts of hexadecylamine and 4 parts of aluminum dihydrogen tripolyphosphate to 15 parts of water, add 30 parts of the mixed solution, stir at room temperature for 2 hours, filter, wash, dry and grind to obtain hexadecylamine intercalated aluminum dihydrogen tripolyphosphate; S5: Mix hexadecylamine intercalated aluminum tripolyphosphate and 3,4-dihydroxycinnamaldehyde in a mass ratio of 5:3 to obtain an intermediate; take 5 parts of the intermediate, 5 parts of 5,6-dibromobenzimidazole, and 2 parts of guar gum hydroxypropyltrimethylammonium chloride, mix them evenly, and obtain a corrosion-resistant antibacterial agent; S6: Take 80 parts of silicone resin, 12 parts of hydrogenated silicone oil, 15 parts of ethanol, 30 parts of nano silicon carbide, and 12 parts of corrosion-resistant antibacterial agent, mix them evenly, and obtain a corrosion-resistant antibacterial coating; S7: The corrosion-resistant and antibacterial coating is applied to the surface of the stainless steel strip A to obtain a corrosion-resistant and antibacterial coating with a thickness of 12 μm, and the stainless steel strip B is obtained by ventilation and drying at room temperature for 2 days; the modified gallium-containing zinc oxide sol is applied to the surface of the stainless steel strip B, and the gallium-containing zinc oxide layer is obtained by treating the surface at 95° C. for 6 h and at 220° C. for 30 min, and the gallium-containing zinc oxide layer is obtained with a thickness of 70 nm, and the wear-resistant duplex stainless steel strip is obtained.

[0027] Comparative Example 4 (the thickness of the corrosion-resistant and antibacterial coating and the gallium-containing zinc oxide layer is changed, and the other method steps are consistent with Example 1): S1: electroplating an iron-nickel-copper layer on the surface of a duplex stainless steel strip to obtain a stainless steel strip A; S2: Take zinc nitrate, zinc acetylacetonate, gallium nitrate and ethanol, stir evenly at 60°C, and age for 24 hours to obtain a gallium-containing zinc oxide sol; wherein the concentration of zinc nitrate in the ratio solution is 0.1 mol / L, the concentration of gallium nitrate is 0.002 mol / L, and the concentration of zinc acetylacetonate is 0.1 mol / L; S3: Take 3 parts of vinyl triethoxysilane, add to 12 parts of water, stir at 50°C for 0.5h, add 100 parts of gallium-containing zinc oxide sol, stir at 50°C for 5h, add 0.008 parts of platinum catalyst, stir evenly, and obtain modified gallium-containing zinc oxide sol; S4: Add 3 parts of hexadecylamine and 4 parts of aluminum dihydrogen tripolyphosphate to 15 parts of water, add 30 parts of the mixed solution, stir at room temperature for 2 hours, filter, wash, dry and grind to obtain hexadecylamine intercalated aluminum dihydrogen tripolyphosphate; S5: Take 10 parts of hexadecylamine intercalated aluminum tripolyphosphate and 150 parts of ether, pressurize and heat to 90°C and stir evenly, add 6 parts of 3,4-dihydroxycinnamaldehyde, stir for 30 minutes, add 3 parts of glacial acetic acid, react for 6 hours, remove the solvent, and obtain an intermediate; take 5 parts of the intermediate, 5 parts of 5,6-dibromobenzimidazole, 2 parts of guar gum hydroxypropyltrimethylammonium chloride, and 3 parts of sodium carbonate, add to 100 parts of ethanol and stir evenly, stir at 78°C for 6 hours, remove the solvent, and obtain a corrosion-resistant antibacterial agent; S6: Take 80 parts of silicone resin, 12 parts of hydrogenated silicone oil, 15 parts of ethanol, 30 parts of nano silicon carbide, and 12 parts of corrosion-resistant antibacterial agent, mix them evenly, and obtain a corrosion-resistant antibacterial coating; S7: The corrosion-resistant and antibacterial coating is applied to the surface of the stainless steel strip A to obtain a corrosion-resistant and antibacterial coating with a thickness of 16 μm, and the coating is dried under ventilation at room temperature for 2 days to obtain a stainless steel strip B; the modified gallium-containing zinc oxide sol is applied to the surface of the stainless steel strip B, and the coating is treated at 95° C. for 6 h and 220° C. for 30 min to obtain a gallium-containing zinc oxide layer with a thickness of 100 nm to obtain a wear-resistant duplex stainless steel strip.

[0028] In the above embodiments, the test methods used are conventional methods unless otherwise specified; the raw materials used are commercially available unless otherwise specified, and the sources of the raw materials are as follows: ethanol (CAS: 64-17-5); sodium carbonate (S24152, Shanghai Yuanye); nickel sulfate hexahydrate (CAS: 10101-97-0); ferric sulfate (CAS: 10028-22-5); copper sulfate pentahydrate (CAS: 7758-99-8); sodium citrate dihydrate (CAS: 6132-04-3); sodium acetate (CAS: 127-09-3); sodium hypophosphite (CAS: 10039-56-2); zinc nitrate (CAS: 7779-88-6); zinc acetylacetonate (CAS: 14024-63-6); gallium nitrate (CAS: 13494-90-1); vinyl triethoxysilane (CAS :78-08-0); ether (CAS: 60-29-7); 3,4-dihydroxycinnamaldehyde (CAS: 68149-78-0); glacial acetic acid (CAS: 64-19-7); 5,6-dibromobenzimidazole (CAS: 74545-26-9); guar hydroxypropyltrimethylammonium chloride (S26747, Shanghai Yuanye); silicone resin (SAR-2, Shanghai Organic Resin Factory); n-propylamine solution (CP, ≥98.5%, Sinopharm Group); platinum catalyst (Article No.: 8598479, Wuhan Kanos Technology Co., Ltd.); hexadecylamine (CAS: 143-27-1); aluminum dihydrogen tripolyphosphate (CAS: 17375-35-8); hydrogenated silicone oil (IOTA616, Anhui Iota Silicone Oil Co., Ltd.); nano silicon carbide (YM-SiC-500Y, Yumu Ningbo New Materials Co., Ltd.).

[0029] Experiment: Take the wear-resistant duplex stainless steel strips prepared in Examples 1 to 3 and Comparative Examples 1 to 4; (1) Use Escherichia coli and Staphylococcus aureus with a bacterial concentration of 10 CFU / mL for antibacterial performance testing; (2) Test the pitting potential; (3) Test the wear resistance on a HT-1000 ball-disc high-temperature friction and wear tester at room temperature, with a Cr15 grinding ball with a diameter of 3.5 mm, a load of 200 N, a time of 20 min, and a motor speed of 560 r / min; see the table below for specific data;

[0030] Conclusion: Comparative Example 1 uses unmodified gallium-containing zinc oxide sol and uses silicone resin instead of hydrogen-containing silicone oil. Due to the weakened interaction between the two layers, the performance is reduced; Comparative Example 2 electroplates an iron-nickel-copper-gallium-zinc layer on the surface of the stainless steel strip without using a gallium-containing zinc oxide layer, and the performance is not as good as the embodiment; Comparative Example 3 changes the preparation method of the corrosion-resistant antibacterial agent: hexadecylamine intercalates dihydrogen tripolyphosphate aluminum, 3,4-dihydroxycinnamaldehyde, 5,6-dibromobenzimidazole, and guar gum hydroxypropyltrimethylammonium chloride are directly added without compounding, and the performance is significantly reduced; Comparative Example 4 increases the thickness of the corrosion-resistant antibacterial coating and the gallium-containing zinc oxide layer, and the performance is reduced due to the influence of bonding force, etc.; In summary, the wear-resistant duplex stainless steel strip prepared by the present invention has good wear resistance, antibacterial and corrosion resistance.

[0031] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

Claims

1. A processing technology for wear-resistant duplex stainless steel strip, characterized in that: The following steps are involved: S1: electroplating an iron-nickel-copper layer on the surface of a duplex stainless steel strip to obtain a stainless steel strip A; S2: taking organic silicone resin, hydrogenated silicone oil, ethanol, nano silicon carbide, and corrosion-resistant antibacterial agent, and mixing them evenly to obtain corrosion-resistant antibacterial coating; S3: coating the surface of the stainless steel strip A with a corrosion-resistant and antibacterial coating, and drying at room temperature to obtain a stainless steel strip B with a corrosion-resistant and antibacterial coating on the surface; coating the surface of the stainless steel strip B with a gallium-containing zinc oxide sol, and heat treating to obtain a wear-resistant duplex stainless steel strip with a gallium-containing zinc oxide layer on the surface.

2. The processing technology of a wear-resistant duplex stainless steel strip according to claim 1, characterized in that: The electroplating process is: pH = 7 ~ 8, temperature 55 ~ 60 ° C, DC current 3 ~ 5A / dm 3 , time 20~30min; the plating solution used for electroplating includes the following components: 40~50g / L nickel sulfate hexahydrate, 20~30g / L ferric sulfate, 30~40g / L copper sulfate pentahydrate, 35~45g / L sodium citrate dihydrate, 25~30g / L sodium acetate, 20~25g / L sodium hypophosphite.

3. The processing technology of a wear-resistant duplex stainless steel strip according to claim 1, characterized in that: The corrosion-resistant and antibacterial coating comprises the following raw materials, calculated by weight: 75-85 parts of organic silicone resin, 10-15 parts of hydrogenated silicone oil, 10-15 parts of ethanol, 25-35 parts of nano silicon carbide, and 10-15 parts of corrosion-resistant and antibacterial agent.

4. The processing technology of a wear-resistant duplex stainless steel strip according to claim 1, characterized in that: The thickness of the corrosion-resistant and antibacterial coating is 10-15 μm; the thickness of the gallium-containing zinc oxide layer is 60-80 nm.

5. The processing technology of a wear-resistant duplex stainless steel strip according to claim 1, characterized in that: The preparation of the corrosion-resistant antibacterial agent comprises the following steps: step 1: adding hexadecylamine and aluminum dihydrogen tripolyphosphate into water, adding a mixed solution of water and organic amine, stirring at room temperature for 1 to 2 hours, filtering, washing, drying and grinding to obtain hexadecylamine intercalated aluminum dihydrogen tripolyphosphate; Step 2: Take hexadecylamine intercalated with aluminum dihydrogen tripolyphosphate and ether, pressurize and heat to 85-90°C and stir evenly, add 3,4-dihydroxycinnamaldehyde, stir for 30-40 minutes, add glacial acetic acid, react for 4-6 hours, remove the solvent, and obtain an intermediate; Step 3: Take the intermediate, 5,6-dibromobenzimidazole, guar gum hydroxypropyltrimethylammonium chloride and sodium carbonate, add them to ethanol and stir evenly, stir at 70-78°C for 5-7h, remove the solvent, and obtain a corrosion-resistant antibacterial agent.

6. A processing technology for wear-resistant duplex stainless steel strip according to claim 5, characterized in that: The hexadecylamine intercalated aluminum trihydrogen phosphate comprises the following raw materials, calculated by weight: 2-3 parts of hexadecylamine, 3-4 parts of aluminum trihydrogen phosphate, and 20-30 parts of a mixed solution; the mixed solution is a solution of water and an organic amine in a volume ratio of (3-4):1; The intermediate comprises the following raw materials, calculated by weight: 8 to 10 parts of hexadecylamine intercalated aluminum dihydrogen tripolyphosphate, 4 to 6 parts of 3,4-dihydroxycinnamaldehyde, and 2 to 3 parts of glacial acetic acid; The corrosion-resistant antibacterial agent comprises the following raw materials, calculated by weight: 4 to 5 parts of an intermediate, 4.5 to 6 parts of 5,6-dibromobenzimidazole, 2 to 3 parts of guar gum hydroxypropyltrimethylammonium chloride, and 2 to 3 parts of sodium carbonate.

7. The processing technology of a wear-resistant duplex stainless steel strip according to claim 1, characterized in that: The preparation of the gallium-containing zinc oxide sol comprises the following steps: Zinc nitrate, zinc acetylacetonate, gallium nitrate and ethanol are taken, stirred evenly at 50-60° C., and aged for 24-25 hours to obtain a gallium-containing zinc oxide sol; in the gallium-containing zinc oxide sol, the concentration of zinc nitrate is 0.1-0.15 mol / L, the concentration of gallium nitrate is 0.002-0.003 mol / L, and the concentration of zinc acetylacetonate is 0.1-0.15 mol / L.

8. The processing technology of a wear-resistant duplex stainless steel strip according to claim 1, characterized in that: The gallium-containing zinc oxide sol is modified to obtain a modified gallium-containing zinc oxide sol and then coated. The preparation of the modified gallium-containing zinc oxide sol includes the following steps: adding vinyl triethoxysilane to water, stirring evenly, adding the gallium-containing zinc oxide sol, stirring at 45-50° C. for 4-6 hours, adding a platinum catalyst, stirring evenly, and obtaining the modified gallium-containing zinc oxide sol; The modified gallium-containing zinc oxide sol comprises the following raw materials, calculated by weight: 2-4 parts of vinyltriethoxysilane, 10-15 parts of water, 100-110 parts of gallium-containing zinc oxide sol, and 0.006-0.008 parts of platinum catalyst.

9. The processing technology of a wear-resistant duplex stainless steel strip according to claim 1, characterized in that: The composition of the duplex stainless steel strip is as follows by mass percentage: C 0.001-0.002%; Cr 23-25%; Mn 8-9%; N 0.5-0.7%; Ni 0.001-0.005%; the remainder is iron and other inevitable impurities.

10. A wear-resistant duplex stainless steel strip prepared according to the processing technology for a wear-resistant duplex stainless steel strip according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Gallium-containing zinc oxide

    CN101124164A

  • Application of organic amine intercalation compound

    CN108722494A

  • Corrosion-resistant antibacterial medical stainless steel and preparation method thereof

    CN115976513A

  • Corrosion-resistant antibacterial stainless steel material and preparation process thereof

    CN118957583A

  • Low toxic coated steel sheet excellent in corrosion resistance of processed part

    JP2000218229A

Cited By

  • High-thermal-conductivity stainless steel for chip support and preparation method of high-thermal-conductivity stainless steel

    CN120809584A

  • High thermal conductivity stainless steel for chip carrier and method for manufacturing the same

    CN120809584B